Evaluation of water quality in Rafsanjan county aqueducts - Mohsen Pourkhosravani; Fatemeh Jamshidi Gohari (Journal of Applied Research in Water and Wastewater)
The present study aimed to assess the water quality of six selected aqueducts using Schoeller and Wilcox diagrams and GIS, including Khanaman, Ahmadabad Daafeh, Saadatabad, Kourke, Kazemabad and Fadak in Rafsanjan in 2018. For the study, statistics and information on water quality indices such as sodium, calcium, magnesium, sulfate; bicarbonate, chlorine, electrical conductivity (EC), total hardness (TH), Arsenic, Nitrate, Ph and total dissolved solids (TDS) for 2018 were received from the Kerman Regional Water Organization (KRWO). The most suitable and unsuitable water quality for drinking and agricultural purposes was determined for the aqueducts of Khenaman and Fadak. From obtained results and Schoeller and Wilcox diagrams, Khenaman aqueduct showed good quality that is acceptable for drinking water (C2-S1). Based on the Schoeller and Wilcox diagrams, the water quality of the Fadak aqueduct ranged from "unsuitable" and "completely unsuitable" to "saline water" (C4-S4). Overall, the groundwater in the study area is generally suitable for irrigation and drinking purposes, with some exceptions that require cautious use. However, evaluating groundwater quality remains essential to ensure its safe and sustainable utilization. Utilizing GIS maps for water quality assessment can enhance the efficiency and accuracy of water quality management, and the water quality database can be easily updated for ongoing monitoring.